PELAKSANAAN PROGRAM CONTINUITY MARKETING DAN ONE TO ONE MARKETING DALAM UPAYA MENINGKATKAN LOYALITAS PELANGGAN ROYAL VANESSA HOTEL (Survei pada tamu repeat individu di Royal Vanessa Hotel Bengkulu) - Putra, Gempur Perdana Adha; Bramantory, Ariyo (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
Indonesia’s tourism industry has developed very rapidly, it’s characterized by the increasing number of tourist both foreign tourists. Form of tourism businesses that are currently experiencing a fairly rapid increase in the hotel industry as tourism support facilities. Customer loyalty is important in the hotel industry. A decline loyalty in Royal Vanessa Hotel is seen from the decrease in occupancy rate repeat guests. Decrease in the level of loyalty is a major threat to the hotel industry because of the presence of this loyalty will decrease the thread indicated a decrease in corporate profits. If a decline in profit the company will have an impact on the company’s losses. Moreover, the adverse effect that will be received from the company is going to decrease the loss of customer loyalty that will turn to another hotel. So do implementation of continuity marketing and one to one marketing program in an effort to increase customer loyalty at the Royal Vanessa Hotel. Respondents of this study is a repeat guest Royal Vanessa Hotel. The method which is used in this research is descriptive and verifikatif, with the survey explanatory method and cross section approach. Sample size of 100 respondents from existing population by using the formula slovin. The data used are primary data and secondary data collected through observation, questionnaires, literature study and interviews. The purpose of this research was to determine how much influence the implementation of continuity marketing and one to one marketing program in an effort to increase customer loyalty at Royal Vanessa Hotel. The results of this study is that there is continuity of influence between the implementation of marketing programs and one to one marketing in an effort to increase customer loyalty at the Royal Hotel Vanessa. Smallest degree of influence in an effort to improve customer loyalty is to the implementation of marketing continuity program, it needs to be fixed by the Royal Hotel with fixing Vanessa Operational Standards (SOP) regarding the marketing continuity program and also the hotel in order to add the programs other than programs that has been done. Thus may increase the effects of the implementation of continuity marketing program in an effort to increase customer loyalty.